2, 2′‐ and 4, 4′‐Cyanines are transporter‐independent in vitro dopaminergic toxins with the specificity and mechanism of toxicity similar to MPP+. (12th August 2015) - Kadigamuwa, Chamila C.; Le, Viet Q.; Wimalasena, Kandatege
Abstract: Specific uptake through dopamine transporter followed by the inhibition of the mitochondrial complex‐I have been accepted as the cause of the specific dopaminergic toxicity of 1‐methyl‐4‐phenylpyridinium (MPP + ). However, MPP + is taken up into many cell types through other transporters, suggesting that, in addition to the efficient uptake, intrinsic vulnerability of dopaminergic cells may also contribute to their high sensitivity to MPP + and similar toxins. To test this possibility, two simple cyanines were employed in a comparative study based on their unique characteristics and structural similarity to MPP + . Here, we show that they freely accumulate in dopaminergic (MN9D and SH‐SY5Y) as well as in liver (HepG2) cells, but are specifically and highly toxic to dopaminergic cells with IC50s in the range of 50–100 nM, demonstrating that they are about 1000‐fold more toxic than MPP + under similar experimental conditions. They cause mitochondrial depolarization non‐specifically, but increase the reactive oxygen species specifically in dopaminergic cells leading to the apoptotic cell death parallel to MPP + . These and other findings suggest that the specific dopaminergic toxicity of these cyanines is due to the inherent vulnerability of dopaminergic cells toward mitochondrial toxins that lead to the excessive production of reactive oxygen species. Therefore, the specific dopaminergic toxicity of MPP + must also be, at least partly, due to the specific vulnerability of dopaminergic neurons. Thus, these cyanines could be stronger in vivo dopaminergic toxins than MPP + and their in vivo toxicities must be evaluated. Here, we show that cationic lipophilic cyanines with structural similarity to 1‐methyl‐4‐phenylpyridinium (MPP + ) freely accumulate non‐specifically, but only toxic to dopaminergic cells. They are 1000‐fold more toxic than MPP + under similar conditions. They cause mitochondrial depolarization non‐specifically, but increase the ROS specifically in dopaminergic cells leading to the apoptotic cell death parallel to MPP + . Thus, the specific dopaminergic toxicity of MPP + and related toxins could be due to the intrinsic vulnerability of dopaminergic cells toward mitochondrial oxidative stress. Abstract : Here, we show that cationic lipophilic cyanines with structural similarity to 1‐methyl‐4‐phenylpyridinium (MPP + ) freely accumulate non‐specifically, but only toxic to dopaminergic cells. They are 1000‐fold more toxic than MPP + under similar conditions. They cause mitochondrial depolarization non‐specifically, but increase the ROS specifically in dopaminergic cells leading to the apoptotic cell death parallel to MPP + . Thus, the specific dopaminergic toxicity of MPP + and related toxins could be due to the intrinsic vulnerability of dopaminergic cells toward mitochondrial oxidative stress.